Analisis Yuridis Tentang Pencabutan Hibah Orang Tua Kepada Anak Kandungnya Dalam Perspektif Perspektif Kompilasi Hukum Islam (Studi Putusan Nomor 1934/Pdt.G/2013/ PA.Mdn) - Mustamam Mustamam (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
A grant is a type of gift made by one person to another when the donor and recipient of the grant is still alive. Grants, in any law, are basically irrevocable unless they meet certain conditions.       A grant is the giving of an object voluntarily and it is done without reward from someone to another person who is still alive to have. A grant cannot be withdrawn except for a grant from the parent to the child, that is to say that the ability to withdraw the grant only applies to parents who donate something to their child. It means that the parents give grants to their children by paying attention to the values of justice.The results of this study indicate that the Religious Court Medan Number 1934 / Pdt.G / 2013 / PA.Mdn which was decided on 26 May 2014 regarding the land given by the grantor was declared revoked or cancelled because the fact shows that first, the life of the grantor at that time was very poor and suffered from diabetes. Second, according to the plaintiff, the grantees had stolen the plantation owner's land certificate. Third, according to witnesses, the grantees refused to support or help the grantor when he was poor. Revocation of this grant is also in accordance with Article 212 of the Compilation of Islamic Law which states that a grant cannot be revoked or cancelled unless it is a grant from the parents to their biological child. This is why the court declared that the grant was null and void. Keywords : Grant, Revocation, Grantor, Grantees.